Magnetic property and structural study of nickel supported on reduced graphene oxide prepared by chemical vapor deposition - Mehravar, S. (John Wiley and Sons Ltd, 2020)
Nickel supported on reduced graphene oxide was synthesized by chemical vapor deposition technique. The crystal structure and magnetic properties of the prepared sample were studied by means of Raman spectrometry, X-ray photoelectron spectroscopy (XPS), transmission electron microscopy (TEM), inductively coupled plasma optical emission spectrometry (ICP-OES), and vibrating sample magnetometry (VSM). The result of Raman spectroscopy revealed the structure of few-layer graphene as the support for Ni nanoparticles. XP spectrum confirmed the presence of metallic Ni on the a few-layer graphene surface. TE micrograph showed that the nickel nanoparticles were sphere shaped and the mean particle size is about 20 nm deposited on the reduced graphene oxide. The magnetic study showed the ferromagnetic behavior of 3.2 wt nickel over reduced graphene oxide at room temperature. Â© 2020 John Wiley & Sons, Ltd.